PERWUJUDAN EKSPRESI KEIMANAN DOA BAPA KAMI MELALUI MODEL COMPLETE SENTENCE LECTORA SISWA TUNARUNGU KELAS V SLB NEGERI 1 BANTUL YOGYAKARTA - Widi Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2021)
One of the prayers that must be mastered by fifth graders is the Lord's Prayer. The limited hearing of deaf students is one of the causes of students' inhibition in mastering the Lord's Prayer at SLB N 1 Bantul. Learning through the Complete Sentence Lectora model aims to improve the ability to express faith through the Lord's Prayer. The initial stage of the Complete Sentence Lectora learning system is carried out orally. The spoken language is then clarified with visual reinforcement in the form of written language from Lectora media. This classroom action research was conducted on the fifth grade deaf students with one student as the respondent. The data obtained through observation, interviews, oral and written tests were processed by qualitative descriptive analysis. The results showed that the Complete Sentence Lectora model could improve the ability of deaf students to express the Lord's Prayer. The system of mastering the Lord's Prayer in the Missal Romanum begins with improving the ability to compose word puzzles, arrange random sentences and then complete missing sentences. The ability to fill in gaps increased from 20% to 65% then in the third stage it reached 95%. Conclusion: The Complete Sentence Lectora method is proven to improve the ability to master the expression of the Lord's Prayer in deaf students. Suggestion: Complete Sentence Lectora method can be applied to rote material that can be expressed